Memory Impairment and Plasma BDNF Correlates of the BDNF Val66Met Polymorphism in Patients With Bipolar II Disorder - Chang, Yun-Hsuan; Wang, Tzu-Yun; Lee, Sheng-Yu; Chen, Shiou-Lan; Huang, Chih-Chun; Chen, Po See; Yang, Yen Kuang; Hong, Jau-Shyong; Lu, Ru-Band (Frontiers in Genetics, 2018)
Studies suggest that a functional polymorphism of brain-derived neurotrophic factor (BDNF), polymorphism BDNF Val66Met affects cognitive functions; however, the effect is unclear in bipolar II (BD-II) disorder. We used the Wechsler Memory Scale-third edition (WMS-III), the presence of the BDNF Val66Met polymorphism, and plasma concentrations of BDNF to investigate the association between memory impairment and BDNF in BD-II disorder. We assessed the memory functions of 228 BD-II patients and 135 healthy controls (HCs). BD-II patients had significantly lower scores on five of the eight WMS-III subscales. In addition to education, the BDNF polymorphism were associated with the following subscales of WMS-III, auditory delayed memory, auditory delayed recognition memory and general memory scores in BD-II patients, but not in HC. Moreover, BD-II patients with the Val-homozygote scored significantly higher on the visual immediate memory subscale than did those with the Met/Met and Val/Met polymorphisms. The significantly positive effect of the Val- homozygote did not have a significantly positive effect on memory in the HC group, however. We found no significant association between BDNF polymorphisms and plasma concentrations of BDNF. The plasma BDNF was more likely to be associated with clinical characteristics than it was with memory indices in the BD-II group. The impaired memory function in BD-II patients might be dependent upon the association between the BDNF Val66Met polymorphism and peripheral BDNF levels.